Prototype Alat Pengantar Makanan Berbasis Arduino Mega - Diah Aryani; Ignatius Joko Dewanto; Alfiantoro Alfiantoro (PETIR, 2019)
The development of Revolution 4.0 is now bringing change to the culinary business process, making culinary entrepreneurs or restaurant owners challenged to be more creative and innovative in order to thrive and survive Industrial Revolution 4.0. One of the culinary world business processes in the 4.0 Industrial Revolution is to provide a contemporary service that is one of them is using robots. This study aims to create a prototype Arduino based food Introduction tool Mega is a new breakthrough in the culinary world with the methods of research among other methods of data collection, methods of designing tools and methods of testing tools. So this prototype can be used to deliver food by using RFID (Radio Frequency Identification) based on instructions from Arduino Mega as a microcontroller, with the command RFID will read the ID on the table and Stepper Motors as a tool drive. So this prototype can be used as a food delivery robot not only as a tool to facilitate the work as well as a tool for the appeal of a restaurant that uses it.